2012
DOI: 10.1093/aje/kws264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Carbohydrate Diets Versus Low-Fat Diets on Metabolic Risk Factors: A Meta-Analysis of Randomized Controlled Clinical Trials

Abstract: The effects of low-carbohydrate diets (≤45% of energy from carbohydrates) versus low-fat diets (≤30% of energy from fat) on metabolic risk factors were compared in a meta-analysis of randomized controlled trials. Twenty-three trials from multiple countries with a total of 2,788 participants met the predetermined eligibility criteria (from January 1, 1966 to June 20, 2011) and were included in the analyses. Data abstraction was conducted in duplicate by independent investigators. Both low-carbohydrate and low-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
259
3
20

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 350 publications
(304 citation statements)
references
References 49 publications
17
259
3
20
Order By: Relevance
“…However, following a low-carbohydrate diet is also associated with increased all-cause mortality, 58 impaired flow-mediated dilatation, 59 and increased LDL-cholesterol levels, 50 although contradictory evidence exists on the latter point. 41 Some researchers have suggest that stressing the modest benefits observed for particular types of diet or macronutrient contents should be discouraged, given the lack of long-term evidence.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, following a low-carbohydrate diet is also associated with increased all-cause mortality, 58 impaired flow-mediated dilatation, 59 and increased LDL-cholesterol levels, 50 although contradictory evidence exists on the latter point. 41 Some researchers have suggest that stressing the modest benefits observed for particular types of diet or macronutrient contents should be discouraged, given the lack of long-term evidence.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 99%
“…No adverse effects were observed after 12 months in patients following the Atkins diet, 40 which was in accordance with the results of previous short-term studies and critical reviews. 22,41,42 However, the authors could not establish whether the increased weight loss was due to the reduced carbohydrate content or the increased amount of protein in the Atkins diet.…”
mentioning
confidence: 99%
“…Finally, carriers of the -308 GG promoter variant of TNF-alpha gene have a better metabolic response than A allele carriers with a high polyunsaturated fat hypocaloric diet (10). On the other hand, recent studies have suggested no major differences between the effects of various dietary approaches, including low-carbohydrate and low-fat diets, on body weight outcomes (11,12). However, other studies have reported that very low-carbohydrate ketogenic diets and the Mediterranean diet are superior to low-fat diets in reducing body weight (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Other literature examining the proportion of fat, carbohydrate, and protein in the diet has found that low carbohydrate was more beneficial for weight loss and did not adversely affect the lipid fractions on a standard metabolic blood profile [16, [25][26][27][28][29][30][31]. While recent studies are examining the role of a high fat diet as a contributing factor for bacterial endotoxins (lipopolysaccharides) which trigger toll-like receptors preparatory to inflammation and inflammation is the key driver for chronic disease of which Type 2 Diabetes Mellitus (T2DM) and obesity are foremost [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…While recent studies are examining the role of a high fat diet as a contributing factor for bacterial endotoxins (lipopolysaccharides) which trigger toll-like receptors preparatory to inflammation and inflammation is the key driver for chronic disease of which Type 2 Diabetes Mellitus (T2DM) and obesity are foremost [28][29][30][31]. Marcos et al state that there are numerous pathological situations where nutrients (fat, carbohydrate, protein, vitamins, minerals) play a primary or secondary determinant role for some underlying immunological impairment of which obesity is now subsumed [32].…”
Section: Introductionmentioning
confidence: 99%